Primary intrathoracic liposarcomas: A clinicopathologic and molecular study of 43 cases in one of the largest medical centers of China - Xie, You; Jing, Wenyi; Zhao, Wei; Peng, Ran; Chen, Min; Lan, Ting; Peng, Heng; He, Xin; Chen, Huijiao; Zhang, Zhang; Zhang, Hongying (Frontiers in Oncology, 2022)
Introduction: Primary intrathoracic liposarcoma is extremely rare, and most published series lack genetic analyses. The aim of our study is to better understand the clinicopathologic and genetic features of these rare lesions. Materials and Methods: Forty-three primary intrathoracic liposarcomas were identified and most cases were analyzed by systematic genetic studies, including fluorescence in situ hybridization (FISH), whole-exome sequencing (WES), and Sanger sequencing. Results: This series included 27 males and 16 females (ratios, 1.68:1) aged 24-73 years (median, 53 years). Tumors mainly occurred in the mediastinum (n=23, 53.5%), followed by pleural cavity (n=16, 37.2%) and lung (n=4, 9.3%). The study included 21 well-differentiated liposarcomas (WDLs), 19 dedifferentiated liposarcomas (DDLs), 2 myxoid pleomorphic liposarcomas (MPLs) and 1 pleomorphic liposarcoma (PL), without identification of myxoid liposarcoma. FISH analysis identified MDM2 amplification in 17 of 18 WDLs (94.4%) and all DDLs (16/16, 100.0%). The MDM2-nonamplified WDL was CDK4-nonamplified but FRS2-amplified. WES and Sanger sequencing found somatic TP53 mutation in the 2 MPLs. Follow-up information was available for 33 of 38 cases (86.8%). Thirteen patients (39.4%) showed no evidence of disease, 10 patients (30.3%) were alive with disease, and 8 patients (24.2%) died of disease. Fourteen cases developed recurrence and 1 with metastasis. Conclusions: WDL/DDL was the overwhelming subtype in this location, followed by MPL and PL. Analysis of the FRS2 gene, in combination with MDM2 and other genes of 12q13-15, may more precisely characterize WDL/DDLs. MPL is the most fatal subtype of this site. Further studies are needed to explore the role of TP53 in the pathogenesis of MPL.